2023
DOI: 10.3389/fenvs.2022.1077565
|View full text |Cite
|
Sign up to set email alerts
|

Gardens of life: Multifunctional and ecosystem services of urban cemeteries in Central Europe and beyond—Historical, structural, planning, nature and heritage conservation aspects

Abstract: Cemeteries are often seen as monofunctional spaces for burial and mourning and, within the dynamically changing urban fabric, as a planning conundrum. Long periods of stability have also turned these untouched and hidden places into refugia for nature and wildlife. In booming and dense cities with high land use pressures and housing shortages, in particular, as the amount of burial ground needed per citizen decreases and burial cultures change, the cemetery has become a contested nature, as a simultaneous spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 125 publications
1
2
0
1
Order By: Relevance
“…Comparing our results with other studies on ecosystem service assessment and integration into water management reveals some common themes as well as some unique insights [42,43]. For example, many studies have highlighted the importance of considering multiple ecosystem services when making decisions about land use or resource management [44][45][46]. Our study adds to this body of literature by providing detailed data on specific ecosystem services in a particular region (the demonstration zone), which can inform local decision making.…”
Section: Synthesis and Interpretation Of Resultssupporting
confidence: 58%
“…Comparing our results with other studies on ecosystem service assessment and integration into water management reveals some common themes as well as some unique insights [42,43]. For example, many studies have highlighted the importance of considering multiple ecosystem services when making decisions about land use or resource management [44][45][46]. Our study adds to this body of literature by providing detailed data on specific ecosystem services in a particular region (the demonstration zone), which can inform local decision making.…”
Section: Synthesis and Interpretation Of Resultssupporting
confidence: 58%
“…Ein Gemeinschaftsgarten wurde gegründet und zahlreiche Aktivitäten mit Kitas und Schulen entwickelt, um mehr zivilgesellschaftliche Akteure einzubeziehen und die Idee der Essbaren Stadt besser in der Bevölkerung zu verankern. In Neukölln wird ein ehemaliger Friedhof im Besitz des Evangelischen Friedhofsverbandes in einer gründerzeitlichen Blockbebauung sanft in einen Ort verwandelt, der die Qualitäten dieser grünen Oasen für die Nachbarschaft erhält und gärtnerische Elemente integriert (Säumel et al, 2023).…”
Section: Andernach: Essbares Stadtgrün Für Alleunclassified
“…Under these conditions, gardens and archaeological sites can serve as "havens" that protect biodiversity from the impacts and stresses associated with urban development (Ceschin et al 2012;Capotorti et al 2013;Caneva et al 2018;Heneidy et al 2022;Säumel et al 2023). Previous research has shown that preserving cultural heritage sites can signi cantly contribute to global biodiversity conservation (Gao et al 2013; Woods et al 2017).…”
Section: Introductionmentioning
confidence: 99%